A contrastive analysis of the structure and order of English and Ilongo adjectives - Reyes, Jesusa Roca 1925- (Quezon City University of the Philippines, 1966)
The classes of adjectives in English and Ilonggo are determined in this study and an analysis of their morphological structure and their order or sequence in speech is also provided. Through the constructive analysis of the morphological structure and the order of English and Ilonggo adjectives, learning problems can be predicted and suggestions can be made to overcome these difficulties.
Thesis (M.A.T.)--University of the Philippines
Keywords: English language -- Adjectives; Ilongo dialect -- Adjective